Oxolinic acid therapy: An effective way to reduce Aeromonas veronii infection in Oreochromis niloticus and improve biochemical and hematological parameters and histopathological lesions - Sinha Priyanka; Abraham Thangapalam Jawahar; Sen Arya; Sharon Joshi; Das Ratnapriya; Ghorai Arpan; Boda Satyanarayana; Patil Prasanna Kumar (Fisheries & Aquatic Life)
Bacterial diseases such as motile Aeromonas septicemia are major constraints on aquaculture. This study evaluated the efficacy of oral oxolinic acid (OA) therapy at 12 mg kg biomass−1 day−1 for seven days to treat Aeromonas veronii-Av-F (AV) infection in Oreochromis niloticus. The lethal dose of AV for 50% mortality was determined to be 1.81 ×108 cells fish−1. Following intramuscular AV infection at 2.47 × 108 cells fish−1, OA treatment significantly reduced fish mortality and accelerated wound healing. AV infection caused notable changes in biochemical, and hematological parameters, erythrocyte morphology, and histopathological damage to liver and kidney tissues. However, OA therapy facilitated normalizing these parameters more rapidly than in untreated fish, including erythrocyte morphology and histopathological alterations. The study highlights the effectiveness of OA in treating AV infection in O. niloticus. However, available evidence cautions against its overuse and violations of regulations because of its critical importance in human medicine.